Genotypic variability of Phytophthora capsici isolates in Guanajuato - Guerrero-Aguilar, Brenda Zulema; Pons-Hernández, José Luis; González-Chavira, Mario Martin; González-Pérez, Enrique; Villalobos-Reyes, Salvador; Rodríguez Guerra, Raúl (Revista Mexicana de Ciencias Agrícolas, 2022)
Phytophthora capsici is the causative agent of ‘chili pepper wilt’ one of the most important diseases of this crop. To establish efficient control strategies, it is necessary to know the diversity of the pathogen, for this, this research was carried out, whose objective was to determine the degree of genetic diversity of 30 monozoosporic isolates obtained from pepper (Capsicum annuum L.) from six municipalities in the state of Guanajuato, and two reference strains. The genetic variation was determined by the AFLP technique. The similarity found between the isolates ranges from 76 to 95%. The results obtained indicate that, within the population, groups form based on the localities of isolation. No clonal organisms were found, so the 32 isolates analyzed were unique genotypes, and no correlation was found between groups defined by molecular markers and virulence, type of mating or response to metalaxyl.